Continued Vigilance – Development of an Online Evaluation Tool for Assessing Preparedness of Medical Facilities for Biological Events - Adini, Bruria; Verbeek, Luzie; Trapp, Susanna; Schilling, Stefan; Sasse, Julia; Pientka, Kathrin; Böddinghaus, Boris; Schaefer, Helene; Schempf, Jörg; Brodt, Reinhard; Wegner, Christian; Lev, Boaz; et al. (Frontiers in Public Health, 2014)
Objective: Effective response to biological events necessitates ongoing evaluation of preparedness. This study was a bilateral German-Israeli collaboration aimed at developing an evaluation tool for assessing preparedness of medical facilities for biological events. Methods: Measurable parameters were identified through a literature review for inclusion in the evaluation tool and disseminated to 228 content experts in 2 modified Delphi cycles. Focus groups were conducted to identify psychosocial needs of the medical teams. Table top and functional exercises were implemented to review applicability of the tool. Results: 117 experts from Germany and Israel participated in the modified Delphi. Out of 188 parameters that were identified, 183 achieved a consensus of >75% of the content experts. Following comments recommended in the Delphi cycles, and feedback from focus groups and hospital exercises, the final tool consisted of 172 parameters. Median level of importance of each parameter was calculated based on ranking recommended in the Delphi process. Computerized web-based software was developed to calculate scores of preparedness for biological events. Conclusions: Ongoing evaluation means, such as the tool developed in the study, can facilitate the need for a valid and reliable mechanism that may be widely adopted and implemented as quality assurance measures. The tool is based on measurable parameters and indicators that can effectively present strengths and weaknesses in managing a response to a public health threat, and accordingly, steps can be implemented to improve readiness. Adoption of such a tool is an important component of assuring public health and effective emergency management. Contact person regarding the evaluation tool: adinib@bgu.ac.il Link to the computerized tool: http://www.be-prep.com/us